2012
DOI: 10.17221/6267-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Atresia coli in a Japanese black calf diagnosed by a barium sulphate enema contrast radiograph in the standing position: a case report

Abstract: A three day-old Japanese black calf was admitted with a history of abdominal distension and absence of defecation. Dilated loops of the small intestine and hypoplasia of the colon and rectum was observed upon a contrast radiographic examination in the standing position. At necropsy atresia coli with undeveloped rectum and patent anal opening was found. We conclude that a contrast radiograph in the standing position is useful for diagnosing atresia coli in such cases.  

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…If cause of atresia has genetic base and/or the affected animal is intended for breeding, surgery is not a useful way due to probably propagation of genetic defects (13). For preventing program, the, parents of the affected foal should be avoided for breeding purpose (12).…”
Section: Resultsmentioning
confidence: 99%
“…If cause of atresia has genetic base and/or the affected animal is intended for breeding, surgery is not a useful way due to probably propagation of genetic defects (13). For preventing program, the, parents of the affected foal should be avoided for breeding purpose (12).…”
Section: Resultsmentioning
confidence: 99%
“…Elsa & Onyeyili (2004) reported two cases of goat kids affected with jejunal atresia corrected successfully by reseating and anastomosing the blind end so that the lumen of the intestine was patent for normal physiological function. Contrary to this, Abouelnasr et al (2012) have stated that in most animals with intestinal atresia like those of proximal sites, surgical treatment is not recommended due to limited accessibility, low chance of postoperative survival rate and economic considerations. Moreover, if the cause of atresia is genetic origin and/or the affected animal is intended for breeding, surgery is not recommended due to probable propagation of genetic defects (Abouelnasr et al, 2012).…”
mentioning
confidence: 99%
“…Contrary to this, Abouelnasr et al (2012) have stated that in most animals with intestinal atresia like those of proximal sites, surgical treatment is not recommended due to limited accessibility, low chance of postoperative survival rate and economic considerations. Moreover, if the cause of atresia is genetic origin and/or the affected animal is intended for breeding, surgery is not recommended due to probable propagation of genetic defects (Abouelnasr et al, 2012). Nonetheless, it has been shown that when the ileocaecal valve is completely absent, ileocaecal anastomosis appears to be sufficient (Cserni et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations